Studi Literatur tentang Strategi Pendidikan Agama Islam dalam Mempromosikan Kerukunan Antar Umat Beragama - Faikhatul Munawaroh; Achmad Hidayatullah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Indonesia is one of the countries that has a lot of diversity and makes this diversity one of the main challenges for society. The presence of PAI is able to help the community in creating a more harmonious life between religious communities and between communities. This study aims to explore PAI strategies in promoting interfaith harmony, given the challenges PAI faces in teaching values of tolerance and respect for differences. The research method employed is a literature review, analyzing previous research findings related to PAI's contribution to social harmony. The findings indicate that PAI can strengthen universal values such as tolerance and respect, play a role in preventing extremism, and promote religious moderation. Identified strategies include the teaching of moderate values, the development of teaching methods that encourage interfaith dialogue and cross-cultural collaboration, and the integration of humanitarian, justice, and peace values into the curriculum. Other strategies emphasize the importance of active participation from various stakeholders in enhancing understanding and appreciation of diversity. By adopting inclusive and dialogical approaches, PAI can effectively serve as an agent of change in building a harmonious and tolerant society amidst religious pluralism.